KOMPETENSI PENDIDIK PAUD PADA LEMBAGA PAUD (KELOMPOK BERMAIN) BINAAN BPKB SULAWESI TENGGARA - Tomo, La Ode (JIV-Jurnal Ilmiah Visi, 2008)
The purpose of this research was to describe the competence of educators in early childhood education institutions in South East Sulawesi. Data were collected using interview guides and document study to be analysed qualitatively. This research concludes the need to improve the educators’ competences and provides some recommendations to do.